Effects of maternal intake of n-3 fatty acids on lipid profile and leptin concentration in cord blood - BEKİROĞLU, GÜLNAZ NURAL; BATIREL, SAİME (MARMARA UNIV, FAC MEDICINE, 2017)
Objectives: Maternal intake of n-3 long chain polyunsaturated fatty acids (LC-PUFAs) has positive effects on fetal development and pregnancy outcomes. Leptin plays an important role in placental transportion of LC-PUFAs. In this study, we aimed to evaluate the effects of maternal n-3 LC-PUFAs intake on anthropometric parameters of mother and newborn, the levels of fatty acids (FAs) and leptin in cord blood. Material and Methods: Thirty-one pregnant women were included. Eighteen were assigned to the control group and 13 received a supplement containing n-3 LC-PUFAs during last trimester of gestation (supplemented group). Physical examinations of the participants were performed and additional data were collected with a questionnaire. FAs and leptin concentrations in cord blood samples were analyzed using gas chromatographymass spectrometry (GC-MS) and enzyme-linked immunosorbent assay (ELISA) kit respectively. Results: A total amount of n-3 PUFAs significantly increased after treatment. n-6/n-3 PUFAs ratios and the leptin levels were lower in the supplemented group (P=0.052, P=0.140 respectively). There were positive correlations between leptin levels and the z scores for birth weight, height and head circumference of the newborns in the control group. The supplementation affected leptin concentration to be positively correlated with n-6/n-3 PUFA ratios. Conclusion: Daily supplementation with n-3 LC-PUFAs might be effective to improve mother and newborn health.
Keywords: Leptin; Fatty acids; Cord blood; Newborn; Pregnancy; PLACENTAL LEPTIN; PLASMA-CONCENTRATIONS; PREGNANCY; SUPPLEMENTATION; ADIPONECTIN; OUTCOMES; INFANT; HEALTH; GROWTH; WOMEN